Training on Using Adanco for SEM-PLS Analysis in Advanced Managerial Research - Tabelessy, Walter; Pattiruhu, Josef Ricky (Indonesian Journal of Advanced Social Works, 2025)
This training was conducted to strengthen the understanding and skills of Master of Management students at Pattimura University in applying Adanco as an SEM-PLS analysis tool. The training took place online on August 29, 2025, and was attended by 38 students. The training included an explanation of basic concepts, hands-on practice with guidance, and the application of case studies using research data. These activities enabled participants to design research models, conduct estimates, and evaluate models based on SEM-PLS cut-off value criteria. The results demonstrated that the training was effective in improving students' methodological competencies while also providing additional analysis software options. Overall, this activity is expected to support the improvement of the quality of students' research and scientific publications